1991
DOI: 10.1039/c39910001564
|View full text |Cite
|
Sign up to set email alerts
|

Regiospecific introduction of four substituents to porphyrin systems at antipodal pyrrolenic positions

Abstract: Electrophilic bromination occurs regiospecifically at the antipodal pyrrolenic ring of free-base porphyrins bearing substituents that fix the aromatic delocalization pathway; this new feature of porphyrin chemistry is not observed in the reactions of the corresponding metalloporphyrins as the pre-requisite bond fixation is only possible in free-base compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
0
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 3 publications
6
66
0
1
Order By: Relevance
“…1; this is in agreement with the conclusion drawn by Crossley et al (1991). Thus, electrophilic bromination occurs regiospecifically at the antipodal pyrrole ring of free-base porphyrin.…”
Section: Commentsupporting
confidence: 81%
See 1 more Smart Citation
“…1; this is in agreement with the conclusion drawn by Crossley et al (1991). Thus, electrophilic bromination occurs regiospecifically at the antipodal pyrrole ring of free-base porphyrin.…”
Section: Commentsupporting
confidence: 81%
“…Callot (1974) suggested that there existed one Br atom per pyrrole ring, but the results reported by Crossley et al (1991) indicated four Br atoms on the antipodal pyrrole tings. In order to resolve this discrepancy, we prepared the title compound, (I), following the literature method (Crossley et al, 1991) and obtained suitable specimens for crystal structure analysis by layering a solution of the title compound in CHC13 with petroleum/piperidine (333-363 K). …”
Section: Commentmentioning
confidence: 99%
“…Electron-withdrawing substituents in the b-positions of the porphyrin ring stabilize both HOMO and LUMO; bulky groups, however, cause severe distortions to the macrocycle and destabilize the HOMO more than the LUMO. In consequence, the HOMO-LUMO energy gap decreases [20,22,[27][28][29][30][31][32][33][34][35][36][37]67] and the Soret band is considerably shifted to lower energy; the Q bands are also shifted to lower energy but to a smaller extent. The magnitude of the red shift and the number of bromine groups on the porphyrin macrocycle showed a linear relationship for the series Mn(III) (Br x TCMPP)Cl (x = 0, 6, or 8).…”
Section: Synthesesmentioning
confidence: 99%
“…The introduction of more than four halogens into these positions on the ring, for example, results in a pronounced decrease in the porphyrin basicity (associated with the electron-withdrawing effect of the b-halogens) and causes severe distortions on the macrocycle (steric effect) [1,[24][25][26][27][28][29][30]. The combined electronic and steric effects decrease the HOMO-LUMO (highest occupied molecular orbitallowest unoccupied molecular orbital) energy gap and consequently alter the reduction potential of the porphyrin [20,22,[28][29][30][31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 98%
“…[37] The UV/Visible spectrum and the resolved h.f. coupling features of species I at ambient temperatures are characteristic of a 2 A 2u electronic ground state while the featureless isotropic signal for species II is characteristic of a 2 A 1u state. Upon sudden lowering of the temperature to 77 K, the h.f. features disappeared and, instead, only two overlapping isotropic resonances for species I and II or II' were visible.…”
Section: Resultsmentioning
confidence: 99%